Un processus de patrimonialisation populaire : la fraise de l’Île d’Orléans sous surveillance médiatique (1900-2000) - Florence Gagnon-Brouillet (Communiquer)
Since the recent distinction between institutional and social heritage has been made, it is now possible to analyze a case of food heritage independent of official certification. This article aims to show how the Île d'Orléans strawberry is part of a social process of transforming food into a popular heritage, thus recognized and valued "from below". In this sense, it is suggested that press discourses participate in the construction of the strawberry's heritage as much as they relay the resulting construct. The analysis presented in this article thus highlights the role of the media in the construction of heritage, notably through the consolidation of the link between place and product.